2021
DOI: 10.4018/ijabim.20210701.oa12
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Recognition Award and Reputation Dimensions on Corporate Reputation Consequences

Abstract: The present study aims to investigate the influence of corporate recognition award and corporate reputation dimensions on corporate reputation consequences which are trust, satisfaction, loyalty, and positive word-of-mouth advertisements. Moreover, the study also shows the mediating impact of corporate reputation between corporate recognition award and satisfaction and loyalty. The results of the study show that corporate recognition award and corporate reputation have significant influence on trust, satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In the corporate context, Mahamudul and Maqbul (2021) conducted a thorough analysis of the multifaceted dimensions inherent in corporate recognition awards, shedding light on their profound implications for shaping corporate reputation and fostering a positive organizational image. Similarly, Frey and Gallus (2017) undertook a comprehensive examination of the economic underpinnings of awards, presenting a conceptual framework aimed at elucidating the strategic ramifications of recognition programs within corporate settings.…”
Section: Impact Of Awards On Operational Excellencementioning
confidence: 99%
“…In the corporate context, Mahamudul and Maqbul (2021) conducted a thorough analysis of the multifaceted dimensions inherent in corporate recognition awards, shedding light on their profound implications for shaping corporate reputation and fostering a positive organizational image. Similarly, Frey and Gallus (2017) undertook a comprehensive examination of the economic underpinnings of awards, presenting a conceptual framework aimed at elucidating the strategic ramifications of recognition programs within corporate settings.…”
Section: Impact Of Awards On Operational Excellencementioning
confidence: 99%
“…Similarly, Limbunan and Daromes (2022) found that managerial and corporate social performance influence corporate reputation of companies listed on stock exchange. On the contrary, the existing literature demonstrates that corporate reputation positively drives word of mouth, customer trust and satisfaction (Fatmawati and Fauzan 2021;Hasan and Hossain 2021). It is apparent that the prior studies on corporate reputation have not been undertaken with much focus on the internal stakeholders, notably employees in construction firms.…”
Section: Accidents In Constructionmentioning
confidence: 99%
“…Although, organizational reputation is a controversial concept because there has been a lack of consensus on the definition and approach of this concept, such as constructs, dimensions, and measurement issues ( Kim and Woo, 2019 ; Hasan and Hossain, 2021 ), political sensitivity, threats and crisis, drivers that influence the public perception of good reputation, reputation’s financial value, relation with leadership commitment, and performance management ( Halligan, 2021 ), and influence issues. The academic literature has failed to provide a clear connection of public organizations’ reputations.…”
Section: Literature Reviewmentioning
confidence: 99%